Keseimbangan Jangka Pendek dan Jangka Panjang Nilai Tukar Rupiah terhadap Dollar Amerika - Horas Djulius; Yudi Nurdiansyah (Faculty of Economics and Business, University of Pasundan, 2014)
Free floating exchange rate system that has been adopted since august 1997 resulted in the strong relationship between macro economic variables with the determination of the exchange rate. Therefore the objective of this research was to explain the effect of these variables to exchange rate in the short run and the long run in the period of 1997 to 2012. The method used was econometrics through error correction model. The research result describes important roles of monetary authority, government and business sector in determining the exchange rate.